“INVESTIGATING THE MECHANISMS AND GENETIC FACTORS INVOLVED IN THE MIGRATION AND NAVIGATION OF AVIAN SPECIES” - Parimala B., and Krishna, (Chelonian Research Foundation, 2024)
: Migration biology is an important chapter of the past decade which includes the wealth and health of descriptive articles that indicate different kinds of emigrational aspects. We must understand the proximate as well as ultimate causes of migration timing, energy distribution, optimized performance, immigration success, and fitness for the purpose of supporting wildlife population management as well as conservation initiatives by putting in place suitable safeguards or controlling environmental variables that affect migration. Different kinds of psychological measurements and dance are an important part by using new and innovative approaches and experimental processes. For hundreds of thousands of generations, humans have been intrigued by birds' extraordinary capacity to travel to faraway locations with accuracy. A unique combination of biological processes and genetic factors organizes this intricate accomplishment. The mechanism of Avi and species are divided into some parts like “Magneto reception”, “Landmark Recognition”, “Sun and Star Navigation”, and “Olfaction”. According to the sensory movement theory, which explains how homing pigeons navigate, birds learn how to connect directions from the wind with breeze-borne scents within their homes and, after being moved, calculate their home orientation based on ambient odors in the area around them. The “migratory movements” are determined mostly in the passerine birds which are mostly presumed as the cultural and social factors that play the largest role in the environmental system. Keywords: navigation, migration, sensory movement theory, Landmark Recognition, homing pigeons